Analytical Model for Classifying Areas of Interest in Interactive Systems - Lima, Danilo Teixeira; Zacarias, Rodrigo Oliveira; de Souza, Kennedy Edson Silva; dos Santos, Rodrigo Pereira; Seruffo, Marcos César da Rocha (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Several organizations have invested in solutions to improve user experience when interacting with computer systems and tools. One of the applied strategies is the study of users behavior in order to identify which areas of interest (AOI) mostly attract their attention in the application interfaces. In this context, this paper proposes an analytical model that defines AOI based on HyperText Markup Language (HTML) objects of the system interface and classifies them based on an algorithm that uses data from the Tracking Techniques Based User Experience Evaluation Tool (T2-UXT). To evaluate the proposal, a feasibility study was carried out on the Amazon portal. Results allow us to visualize a ranking of areas that mostly attract attention from users during the interaction. As such, it can assist organizations in the creation of interacting ways that benefit their interests as well as their customers' interests.